Modified enzymes for reactions in organic solvents - Salleh, A B; Basri, M; Taib, M; Jasmani, H; Rahman, R N Z A; Rahman, M B A; Razak, C N A (Springer, 2002)
Recent studies on biocatalysis in water—organic solvent biphasic systems have shown that many enzymes retain their catalytic activities in the presence of high concentrations of organic solvents. However, not all enzymes are organic solvent tolerant, and most have limited and selective tolerance to particular organic solvents. Protein modification or protein tailoring is an approach to alter the characteristics of enzymes, including solubility in organic solvents. Particular amino acids may play pivotal roles in the catalytic ability of the protein. Attaching soluble modifiers to the protein molecule may alter its conformation and the overall polarity of the molecule. Enzymes, in particular lipases, have been chemically modified by attachment of aldehydes, polyethylene glycols, and imidoesters. These modifications alter the hydrophobicity and conformation of the enzymes, resulting in changes in the microenvironment of the enzymes. By these modifications, newly acquired properties such as enhancement of activity and stability and changes in specificity and solubility in organic solvents are obtained. Modified lipases were found to be more active and stable in organic solvents. The optimum water activity (a w ) for reaction was also shifted by using modified enzymes. Changes in enantioselective behavior were also observed.